Retrieval augmented generation with the OpenAI API & DuckDB - Vankrunkelsven, Vincent (Packt Publishing, 2025)
Build an advanced movie database search bot using Retrieval-Augmented Generation (RAG). In this notebook, you'll learn to enhance GPT's capabilities by integrating factual context through embeddings stored in DuckDB. Utilize OpenAI's gpt-4o-mini for generating responses, and the text-embedding-3-large model for accurate context retrieval. Explore the practical application of LangChain to seamlessly interact with both GPT and the vector database. By embedding IMDb movie descriptions, you'll create a chatbot capable of providing precise answers to movie-related queries. This hands-on project demonstrates efficient methods to improve the factual accuracy of language model outputs without retraining or fine-tuning.
"DataLab" : DataLab is a learning solution designed to empower individuals and teams to explore data, build skills, and solve real-world problems. With interactive content, hands-on exercises, and a focus on practical application, DataLab helps learners turn data curiosity into confident capability-no matter where they start. - Online resource; title from title details screen (O'Reilly, viewed April 10, 2025)
Keywords: Chatbots; Information retrieval -- Computer programs; Motion pictures -- Databases; Artificial intelligence -- Computer programs; Natural language processing (Computer science); Machine learning; Intelligence artificielle; Logiciels; Traitement automatique des langues naturelles; Apprentissage automatique; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet